Transendothelial Insulin Transport is Impaired in Skeletal Muscle Capillaries of Obese Male Mice. Issue 2 (5th January 2020) - Williams, Ian M.; McClatchey, P. Mason; Bracy, Deanna P.; Bonner, Jeffrey S.; Valenzuela, Francisco A.; Wasserman, David H.
Abstract : Objective: The continuous endothelium of skeletal muscle (SkM) capillaries regulates insulin's access to skeletal myocytes. Whether impaired transendothelial insulin transport (EIT) contributes to SkM insulin resistance (IR), however, is unknown. Methods: Male and female C57/Bl6 mice were fed either chow or a high‐fat diet for 16 weeks. Intravital microscopy was used to measure EIT in SkM capillaries, electron microscopy to assess endothelial ultrastructure, and glucose tracers to measure indices of glucose metabolism. Results: Diet‐induced obesity (DIO) male mice were found to have a ~15% reduction in EIT compared with lean mice. Impaired EIT was associated with a 45% reduction in endothelial vesicles. Despite impaired EIT, hyperinsulinemia sustained delivery of insulin to the interstitial space in DIO male mice. Even with sustained interstitial insulin delivery, DIO male mice still showed SkM IR indicating severe myocellular IR in this model. Interestingly, there was no difference in EIT, endothelial ultrastructure, or SkM insulin sensitivity between lean female mice and female mice fed a high‐fat diet. Conclusions: These results suggest that, in male mice, obesity results in ultrastructural alterations to the capillary endothelium that delay EIT. Nonetheless, the myocyte appears to exceed the endothelium as a contributor to SkM IR in DIO male mice.